PEMANFAATAN LIMBAH TANAMAN UNTUK BUDIDAYA SAYURAN DI DESA AIR MESU KABUPATEN BANGKA TENGAH - Lestari, Tri; Kartika, Kartika; Zasari, Maera (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2024)
Air Mesu village is a production center for horticultural products, especially durian fruit, in Central Bangka Regency. This service activity aims to provide training assistance in making block compost and liquid organic fertilizer (POC) for vegetable cultivation. The activity was conducted in Air Mesu village, Pangkalan Baru District, Central Bangka Regency, Bangka Belitung Islands Province. The service activities carried out go through 3 (three) activity stages: training in making compost blocks/soil blocks, liquid organic fertilizer (POC), and vegetable cultivation techniques. The results of implementing the vegetable cultivation technology package by combining vegetable cultivation techniques with the use of plant waste. Through this community empowerment program, we can reduce the use of chemical fertilizers which endanger health and damage the environment. The use of chemical fertilizers can be replaced with compost, or liquid organic fertilizer (POC). Socialization activities are carried out using interactive presentation and discussion methods which include all questions and positive responses from guests/audience